Plant-fungal association in trees: Insights into changes in ecological strategies of Peroneutypa scoparia (Diatrypaceae) - de Errasti, Andres (2014)
Fungal endophytes comprise a highly diverse group of particular interest for their relevant implications to the ecosystems they inhabit. The objective of this study was to infer the phylogenetic affinity between strains of Peroneutypa scoparia exhibiting different lifestyles to elucidate possible shifts in ecological roles. Specimens and living cultures used in the present study were obtained from decaying wood and from live stem tissues of the invasive host species Broussonetia papyrifera. The similarity between the fungal strains was studied through molecular analyses. The results showed a close phylogenetic link and high genetic similarity between endophytic and saprotrophic strains. The main findings suggest that P. scoparia has primary access to the substrate as an endophyte and then, this organism may change its use of the available resources presenting a saprotrophic growth. These results provide valuable information about the roles that diatrypaceous fungi play as endophytes or as decaying wood inhabitants and contributes to evaluate the ecological significance of this group.